2012
DOI: 10.1128/jvi.00282-12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of VP1-Specific Protein Sequence Motifs on Adeno-Associated Virus Type 2 Intracellular Trafficking and Nuclear Entry

Abstract: Adeno-associated virus type 2 (AAV2) has gained much interest as a gene delivery vector. A hallmark of AAV2-mediated gene transfer is an intracellular conformational change of the virus capsid, leading to the exposure of infection-relevant protein domains. These protein domains, which are located on the N-terminal portion of the structural proteins VP1 and VP2, include a catalytic phospholipase A 2 domain and three clusters of basic amino acids. We have identified additional protein seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 64 publications
5
91
0
1
Order By: Relevance
“…S5). Of note, silencing of these genes also increased transduction of ΔVP1-ssAAV2 particles, which are strongly impaired in intracellular trafficking (30). However, transduction was significantly lower than that of wild-type AAV vectors ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…S5). Of note, silencing of these genes also increased transduction of ΔVP1-ssAAV2 particles, which are strongly impaired in intracellular trafficking (30). However, transduction was significantly lower than that of wild-type AAV vectors ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In fact, recent work by Popa-Wagner et al identified a PDZ-binding motif on VP1 that, when mutated, rendered AAV2 defective in nuclear entry. They concluded that this AAV2 PDZ binding domain might initiate signaling pathways within the cell to facilitate nuclear entry (49). Moreover, previous work has shown that AAV2 can interact with the nucleolar proteins nucleophosmin and nucleolin (27,90,91), suggesting that rAAV2 can translocate into the nucleus through interaction with these proteins.…”
Section: Discussionmentioning
confidence: 96%
“…In a study utilizing wt AAV2 in the presence of adenovirus, inhibition of nuclear entry via the NPC through use of the calcium channel inhibitor thapsigargin did not prevent the appearance of viral genomes in the nucleus but did affect the level of nuclear accumulation and replication (48). Recently, a PDZbinding domain was discovered on the N terminal of VP1 that was shown to be important for nuclear entry of wt AAV2 (49). While the current study was under review, a recent study revealed that AAV2 that had been acidified and then neutralized could cause nuclear envelope breakdown in permeabilized HeLa cells (50).…”
Section: A Deno-associated Virus (Aav) Is a Dependovirus In The Familymentioning
confidence: 99%
“…Interaction with cellular proteases and pH-activated autohydrolysis have also been implicated in the entry process (39). In vitro studies typically use a heat pulse as a surrogate for cellular triggers of VP1u and VP1/2 externalization, although characterization of capsids after heating has primarily been limited to antibody detection and electron microscopy (EM) studies (34,(40)(41)(42)75).…”
mentioning
confidence: 99%